Empowering Vulnerable Children through Community Involvement: Mehreen Ashraf, Syed Manzoor Hussain Shah - Mehreen Ashraf,; Syed Manzoor Hussain Shah, (JELM, 2023)
The impediments on the road to development in developing countries include various socio-economic problems. Amongst them, a grave social problem is posed by vulnerable children living in abject poverty. In a number of these countries, such as Pakistan, viability of community involvement and participation for their support is yet to be fully explored. This paper attempts to address the empowerment of vulnerable children in the paradigm of community involvement in the study area. The study was conducted in the four union councils namely Wahndoo, Kali Subah, Kotali Nawab and Swawa of tehsil Kamoki, Gujranwala. The methods employed were both qualitative and quantitative utilizing interview and structured questionnaires with both open and close ended questions as data collection technique. The study has investigated 40% (51) mothers/guardians of orphans were selected by means of simple random sampling and 200 community members using stratified random sampling. A questionnaire was developed and administered to the community members of Kamoki. The mothers/guardians of orphans were interviewed. The research suggested the need to sensitize and mobilize local community to care and support vulnerable children by strengthening the economic capacity of the mothers/guardians.